1978
DOI: 10.1079/bjn19780025
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of use of nitrogen from dried microbial cells after a period of N deprivation in growing pigs

Abstract: 1. Semi-synthetic diets, with dried microbial cells (Pruteen) as the nitrogen source, were used to measure N retention in 50 kg pigs which had been given only sufficient N (5.3 g/d) to maintain N equilibrium for the previous 12 d. Control pigs were given 33.2 gN/d. 2. Metabolic faecal N losses were 1.62 g/d (1.2 g/kg dry matter eaten) and endogenous urinary losses were 3.90 g/d. 3. Realimentation of N-deprived pigs was achieved with diets providing 20.0, 33.2 and 67.4 g N/d and daily rates for N retention were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 8 publications
1
11
1
Order By: Relevance
“…It seems that the amount of nitrogen excreted daily, by pigs at zero nitrogen intake, may underestimate the amount which would inevitably be lost from the tissues of growing animals. In addition to this, the estimate of urinary total N loss of pigs fed the protein-free diet in the present study was low compared to equivalent estimates in the literature (van Es 1972;Whittemore & Fawcett 1976;Fuller & Crofts 1977;D'Mello et al 1976;Whittemore et al 1978). Present findings also indicate that urinary urea N was 0.18 of urinary total N for pigs on the protein-free diet, which was a low proportion compared to that of 0.30 measured on malnourished human subjects (Platt & Heard 1958).…”
Section: Resultscontrasting
confidence: 80%
“…It seems that the amount of nitrogen excreted daily, by pigs at zero nitrogen intake, may underestimate the amount which would inevitably be lost from the tissues of growing animals. In addition to this, the estimate of urinary total N loss of pigs fed the protein-free diet in the present study was low compared to equivalent estimates in the literature (van Es 1972;Whittemore & Fawcett 1976;Fuller & Crofts 1977;D'Mello et al 1976;Whittemore et al 1978). Present findings also indicate that urinary urea N was 0.18 of urinary total N for pigs on the protein-free diet, which was a low proportion compared to that of 0.30 measured on malnourished human subjects (Platt & Heard 1958).…”
Section: Resultscontrasting
confidence: 80%
“…(2003) reported that the change in BUN levels was lower in the pigs previously fed a protein‐deficient diet than pigs previously fed a normal diet. Also, Whittemore et al . 1978) reported that animals fed protein‐deficient diets have reduced nitrogen breakdown and excretion.…”
Section: Resultsmentioning
confidence: 95%
“…However, there were no significant differences (P >0.05) among the experimental diets on glucose, IgG, WBC, RBC and lymphocyte. Whittemore et al (1978) and Whang et al (2003) found that the BUN levels or N breakdown and excretion were lower in the pigs fed a proteindeficient diet than those that were fed a normal diet. For unknown reasons, results from the current experiment showed similar results to those reported by Whittemore et al (1978) and Whang et al (2003).…”
Section: Discussionmentioning
confidence: 99%